2024
DOI: 10.1007/s40328-024-00434-1
|View full text |Cite
|
Sign up to set email alerts
|

The Pannon LitH2Oscope magnetotelluric array in the Pannonian Basin

Tibor Rubóczki,
Attila Novák,
Nóra Liptai
et al.

Abstract: The Pannonian Basin is one of the best natural laboratories in the world to study the lithospheric response to continental extension and subsequent tectonic inversion. Here we address the topic of lithospheric structure by a combined geochemical and magnetotelluric analysis, which has been carried out in the framework of the Pannon LitH2Oscope project. The main objective was to detect the resistivity distribution over the entire lithosphere by magnetotelluric measurements, considering the lithological resistiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…In the study area (see Figure 2), the Miocene calc-alkaline arc magmatism, possibly related to a slab breakoff (Seghedi et al, 2004), was localized along the inner part of the Carpathian fold belt and affected the northern part of the Pannonian Basin. Using 2-D magnetotelluric profiling Patkó et al (2021) have shown that the volcanic field in the inner part of the Western Carpathians (Hungary) is connected to a deep sublithospheric magmatic source region by an electrically conductive conduit interpreted as a zone of metasomatism and/or partial melting, which is supported by a recent study by Rubóczki et al (2024).…”
Section: Introductionmentioning
confidence: 63%
“…In the study area (see Figure 2), the Miocene calc-alkaline arc magmatism, possibly related to a slab breakoff (Seghedi et al, 2004), was localized along the inner part of the Carpathian fold belt and affected the northern part of the Pannonian Basin. Using 2-D magnetotelluric profiling Patkó et al (2021) have shown that the volcanic field in the inner part of the Western Carpathians (Hungary) is connected to a deep sublithospheric magmatic source region by an electrically conductive conduit interpreted as a zone of metasomatism and/or partial melting, which is supported by a recent study by Rubóczki et al (2024).…”
Section: Introductionmentioning
confidence: 63%